2009
DOI: 10.1007/s00431-009-1042-9
|View full text |Cite
|
Sign up to set email alerts
|

Ochoa syndrome: a spectrum of urofacial syndrome

Abstract: The urofacial syndrome, also known as Ochoa syndrome, is a rare autosomal recessive condition that occurs in both genders and characterized by uropathy and facial abnormalities. Early diagnosis is crucial for the management and prognosis of urinary problems due to a dysfunctional bladder. We report 11 patients with urofacial syndrome in five families from Turkey with a median follow up of 32 months (range, 2-44 months).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 6 publications
(18 reference statements)
0
19
0
3
Order By: Relevance
“…Elejalde reported this urofacial syndrome for the first time in 7 children and called the syndrome "Ochoa syndrome" [4]. Until now, several patients with UFS from various countries throughout the world have been reported [5][6][7][8][9]. The disease is characterized by diurnal or nocturnal enuresis, urinary tract infection, voiding dysfunctions resulting from neurogenic bladder, and renal insufficiency resulting from unilateral/bilateral vesicoureteral reflux together with voiding dysfunction.…”
Section: Wilms Tumor (Wt) Is the Most Common Form Of Renal Tumor In Cmentioning
confidence: 93%
“…Elejalde reported this urofacial syndrome for the first time in 7 children and called the syndrome "Ochoa syndrome" [4]. Until now, several patients with UFS from various countries throughout the world have been reported [5][6][7][8][9]. The disease is characterized by diurnal or nocturnal enuresis, urinary tract infection, voiding dysfunctions resulting from neurogenic bladder, and renal insufficiency resulting from unilateral/bilateral vesicoureteral reflux together with voiding dysfunction.…”
Section: Wilms Tumor (Wt) Is the Most Common Form Of Renal Tumor In Cmentioning
confidence: 93%
“…They both had large trabeculated bladder without VUR and one also had high Scr as in our patient. Aydogdu et al reported 16 and 19 year old brothers with UFS, presenting with elevated sCr levels in their series (9). Five of nine cases reported by Varlam and Dippell had CRF and one had end-stage kidney disease (12).…”
Section: Discussionmentioning
confidence: 90%
“…However, there are still some UFS families the members of which had none of these mutations. In addition, some family members with the same mutation may have no grimacing but BD or may have no BD but just characteristic grimacing while their siblings have full-blown UFS in some series (3,9).…”
Section: Discussionmentioning
confidence: 99%
“…Ochoa's or urofacial syndrome, observed in both genders, includes a congenital NNNB together with an abnormal grimace upon smiling, laughing, or crying and bilateral weakness in the distribution of the facial nerve and, in the majority of these patients, nocturnal lagophthalmos, which is described as the inability to close the eyelids during sleep [123][124][125]. The urethral walls contract at the same time as the detrusor.…”
Section: Other Miscellaneous Incontinences Without Urologic or Neurolmentioning
confidence: 98%